Lyrics Videos to Ease the Pronunciation Problem of Indonesian EFL Learner - Dewi Rohmawati; Tono Suwartono (ELLITE, 2019)
Pronunciation is a basic for speaking skill. Rare in Senior High School, neither the teacher pay attention with the students’ pronunciation skill nor give them such media. This study was intended to investigate the effectiveness of lyrics video for teaching English pronunciation in Senior High School. This was quasi experimental study and the population was the second grade students. Reading aloud was given to the students as the pronunciation test. Their voice was recorded while they did the test. Since it was subjective test, so that inter-rater is used to avoid subjectivity in getting students’ score. The score was analyzed using T-test. In the end the result revealed that t-value (2.05) was higher than statistical value of t-table (1.676) at the significant level 5%. Therefore, the students who were taught using lyrics video of English song had better achievement in pronunciation rather than those who were not taught using lyrics video of English song.